Postoperative use of slow-release opioids: The impact of the Australian and New Zealand College of Anaesthetists/Faculty of Pain Medicine position statement on clinical practice. Issue 6 (November 2020) - Tan, Adeline CH; Bugeja, Bernadette A; Begley, David A; Stevens, Jennifer A; Khor, Kok-Eng; Penm, Jonathan
Dose titration with immediate-release opioids is currently recommended for acute pain. The Australian and New Zealand College of Anaesthetists and the Faculty of Pain Medicine released a statement in March 2018 supporting their use in the treatment of opioid-naïve patients; however, the impact of this statement on clinical practice is currently unknown. This retrospective cohort study was conducted to compare opioid prescribing patterns before and after the release of the recommendations. Data were collected on 184 patients (2017, n  = 78; 2018, n  = 106) admitted to the Prince of Wales Hospital in November 2017 and 2018, which consisted of demographic data, opioid prescriptions and discharge opioid information. The main outcome is the number of prescriptions of slow-release opioids in 2017 versus 2018 after the recommendations were published. Confounding factors were accounted for using logistic and multiple regression as appropriate. There was a 29% decrease in slow-release opioid prescriptions during hospitalisation ( n  = 31, 40% versus n  = 12, 11%; P  < 0.001) and 17% decrease at discharge ( n  = 20, 26% versus n  = 9, 9%; P  = 0.02) post-publication. After adjusting for confounders, the odds of slow-release opioids being prescribed postoperatively and at discharge reduced by 86% and 88%, respectively (postoperative period: odds ratio 0.14, P  < 0.05; discharge: odds ratio 0.12, P  < 0.05). In addition, orthopaedic patients were more likely to receive slow-release opioids, consistent with existing literature. As the use of slow-release opioids has been associated with increased harm and protracted opioid use compared to immediate-release opioids, it is hoped that wider dissemination of these recommendations and a change in prescribing practice can be a step towards overcoming the opioid crisis.